Characterisation of Human Hsj1a : an HSP40 molecular chaperone similar to Malarial Pfj4 - McNamara, Caryn (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
Protein folding, translocation, oligomeric rearrangement and degradation are vital functions to obtain correctly folded proteins in any cell. The constitutive or stress-induced members of each of the heat shock protein (Hsp) families, namely Hsp70 and Hsp40, make up the Hsp70/Hsp40 chaperone system. The Hsp40 J-domain is important for the Hsp70-Hsp40 interaction and hence function. The type-II Hsp40 proteins, Homo sapiens DnaJ 1a (Hsj1a) and Plasmodium falciparum DnaJ 4 (Pfj4), are structurally similar suggesting possible similar roles during malarial infection. This thesis has focussed on identifying whether Hsj1a and Pfj4 are functionally similar in their interaction with potential partner Hsp70 chaperones. Analysis in silico also showed Pfj4 to have a potential chaperone domain, a region resembling a ubiquitin-interacting motif (UIM) corresponding to UIM1 of HsjIa, and another highly conserved region was noted between residues 232-241. The highly conserved regions within the Hsp40 J-domains, and those amino acids therein, are suggested to be responsible for mediating this Hsp70-Hsp40 partner interaction. The thermosensitive dnaJ cbpA Escherichia coli OD259 mutant strain producing type-I Agrobacterium tumefaciens DnaJ (AgtDnaJ) was used as a model heterologous expression system in this study. AgtDnaJ was able to replace the lack of two E coli Hsp40s in vivo, DnaJ and CbpA, whereas AgtDnaJ(H33Q) was unable to. AgtDnaJ-based chimeras containing the swapped J-domains of similar type-II Hsp40 proteins, namely Hsj1Agt and Pfj4Agt, were also able to replace these in E. coli OD259. Conserved J-domain amino acids were identified and were substituted in these chimeras. Of these mutant proteins, Hsj IAgt(L8A), Hsj1Agt(R24A), Hsj1Agt(H31Q), Pfj4Agt(L 11A) and Pfj4Agt(H34Q) were not able to replace the E. coli Hsp40s, whilst Pfj4Agt(Y8A) and Pfj4Agt(R27A) were only able to partially replace them. This shows the leucine of helix I and the histidine of the loop region are key in the in vivo function of both proteins and that the arginine of helix II is key for Hsj1a. The histidine-tagged Hsj1a protein was also successfully purified from the heterologous system. The in vitro stimulated ATPase activity of human Hsp70 by Hsj1a was found to be approximately 14 nmol PÃ[subscript]/min/mg, and yet not stimulated by Pfj4, suggesting a possible species-specific interaction is occurring.
Keywords: Heat shock proteins; Protein folding; Proteins -- Analysis; Proteins -- Structure; Plasmodium; Malaria; Molecular chaperones